2018
DOI: 10.1145/3274349
|View full text |Cite
|
Sign up to set email alerts
|

'The Perfect One'

Abstract: Animated GIFs are increasingly popular in text-based communication. Finding the perfect GIF can make conversations funny, interesting, and engaging, but GIFs also introduce potentials for miscommunication. Through 24 in-depth qualitative interviews, this empirical, exploratory study examines the nuances of communication practices with animated GIFs to better understand why and how GIFs can send unintentional messages. We find participants leverage contexts like source material and interpersonal relationship to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In addition, several studies [39], [40] devised methods to predict viewers' sentiments towards animated GIFs. Despite viewer engagement, in [41], it was concluded that viewers may have diverse interpretations of animated GIFs used in communication. They predicted facial expressions, histograms, and aesthetic features and then compared them to those in [40] to determine the most appropriate video features for expressing useful emotions in GIFs.…”
Section: Animated Gif Generation Methodsmentioning
confidence: 99%
“…In addition, several studies [39], [40] devised methods to predict viewers' sentiments towards animated GIFs. Despite viewer engagement, in [41], it was concluded that viewers may have diverse interpretations of animated GIFs used in communication. They predicted facial expressions, histograms, and aesthetic features and then compared them to those in [40] to determine the most appropriate video features for expressing useful emotions in GIFs.…”
Section: Animated Gif Generation Methodsmentioning
confidence: 99%
“…Some mixed-method studies analyze manipulative rhetorics in factoid online articles (Tian et al, 2022), or interpret lexical markers of minority stress experience in LGBTQ+ communities on Reddit (Saha et al, 2019). Qualitative approaches focus on, for example, examining narration and expression of grief and the role of sociotechnical features on TikTok (Eriksson Krutröck, 2021), analyzing potential misunderstandings when using animated graphics interchange formats (GIFs) in nonverbal social media communication (Jiang et al, 2018), or showing how LOLspeak is important for humorous communication in gendered interaction during Hackathons (Brooke, 2022).…”
Section: Background and Related Workmentioning
confidence: 99%
“…While new emojis are being continuously designed to represent various objects and events, they primarily focus on representing emotions. Animated GIFs are another popular way of sharing emotions [5,23]. However, animated GIFs mostly focus on funny memes and might not be supportive enough for expressing diverse chat scenarios.…”
Section: Related Work 21 Diversifying Expressions On Mobile Chatsmentioning
confidence: 99%
“…Emojis are good to express emotions and are often used in social communication [26, 27, 30-32, 35, 41, 56, 59]. Memes, or animated GIFs, are popular for trendy and funny images [5,22,23]. Personal images [11,29] are useful in sharing deep personal and social context.…”
Section: Introductionmentioning
confidence: 99%